2019
DOI: 10.1016/j.omtm.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate Enhances AAV Vector-Mediated Genome Editing in Glycogen Storage Disease Type Ia

Abstract: Glycogen storage disease type Ia (GSD Ia) is a rare inherited disease caused by mutations in the glucose-6-phosphatase (G6Pase) catalytic subunit gene ( G6PC ). Absence of G6Pase causes life-threatening hypoglycemia and long-term complications because of the accumulations of metabolic intermediates. Bezafibrate, a pan-peroxisome proliferator-activated receptor (PPAR) agonist, was administered in the context of genome editing with a zinc-finger nuclease-containing vector (AAV-ZFN) and a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Activation of autophagy is critical for energy utilization and clearance of intracellular lipid, which can preferentially hydrolyze intrahepatic lipid droplets to promote mitochondrial fatty acids β ‐oxidation 101 . A number of previous studies have demonstrated the use of drugs to promote hepatic autophagy in the treatment of GSDIa mice, such as VK2809, fenofibrate as well as bezafibrate 69,71,102 . Recently, mediator complex subunit 1 (MED1) has play an important role in regulating hepatic autophagy, β ‐oxidation of fatty acids, and mitochondrial function 103 .…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of autophagy is critical for energy utilization and clearance of intracellular lipid, which can preferentially hydrolyze intrahepatic lipid droplets to promote mitochondrial fatty acids β ‐oxidation 101 . A number of previous studies have demonstrated the use of drugs to promote hepatic autophagy in the treatment of GSDIa mice, such as VK2809, fenofibrate as well as bezafibrate 69,71,102 . Recently, mediator complex subunit 1 (MED1) has play an important role in regulating hepatic autophagy, β ‐oxidation of fatty acids, and mitochondrial function 103 .…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“… 101 A number of previous studies have demonstrated the use of drugs to promote hepatic autophagy in the treatment of GSDIa mice, such as VK2809, fenofibrate as well as bezafibrate. 69 , 71 , 102 Recently, mediator complex subunit 1 (MED1) has play an important role in regulating hepatic autophagy, β -oxidation of fatty acids, and mitochondrial function. 103 The effect of MED1 on glycogen storage disease has not been studied and it may be an alternative drug for glycogen storage disease.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…154 Intriguingly, the addition of bezafibrate to induce autophagy during genome editing of G6pc À/À mice more effectively corrected the liver abnormalities of GSD Ia, achieving normal G6Pase activity in liver and widespread transduction of hepatocytes. 158 More recently, CRISPR/ Cas9 based genome editing has been used to correct a mutation causing GSD Ia in mice. 159 Instead of inserting a full length transgene, they targeted the most common mutation in GSD Ia patients, G6PC-p.R83C, which represents 32% of all diseased alleles in humans.…”
Section: Preclinical Development Of Gene Therapy and Genome Editing F...mentioning
confidence: 99%
“…An initial genome editing study used a zinc finger nuclease (ZFN) mediated genome editing method, which demonstrated an advantage for genome editing in comparison with gene replacement therapy 154 . Intriguingly, the addition of bezafibrate to induce autophagy during genome editing of G6pc −/− mice more effectively corrected the liver abnormalities of GSD Ia, achieving normal G6Pase activity in liver and widespread transduction of hepatocytes 158 . More recently, CRISPR/Cas9 based genome editing has been used to correct a mutation causing GSD Ia in mice 159 .…”
Section: Preclinical Research In Gsd Gene Therapymentioning
confidence: 99%
“…One example is a recent report showing that bezafibrate not only induced hepatic autophagy but also potentiated rAAV-mediated genome editing in GSD-Ia. 69 Before we establish the safety and efficacy of autophagy modulators in clinical settings, however, tight metabolic control which possibly improves hepatic autophagy in GSD-Ia may be an essential prerequisite for successful gene therapy in GSD-Ia ( Figure 4).…”
Section: Potential Role Of Autophagy In Gene Therapy In Gsd-iamentioning
confidence: 99%